ORGANIZATIONAL AMBIDEXTERITY AND ITS ROLE IN ENTREPRENEURIAL BEHAVIOR THROUGH ORGANIZATIONAL CONSEQUENCE AS AN INTERACTIVE VARIABLE-AN ANALYSIS OF THE OPINIONS OF A SAMPLE OF EMPLOYEES OF THE IRAQI MINISTRY OF HEALTH - Wardah Albdukhaleq Albdurahman Alhamawndi; Omar Khazaal Khudhair (Scholars Digest Publishing, 2025)
Organizational ingenuity is one of the modern topics that enable organizations to achieve a high level of work performance while affecting the behavior of employees by motivating them to overcome any internal or external organizational obstacles in work and thus achieving their objectives through which to serve the community. Purpose of the study: The ability of the reality of organizational ingenuity in distinct behavior through organizational consequences and how the organizational consequences contribute to achieving ingenuity in the organization to reach the required entrepreneurial behavior. The research sample: The sample was represented by (102) administrative leaders who are related to the research subject for the purpose of indicating the extent of the researched ministry's use of organizational ingenuity to demonstrate the distinctive behavior through the organizational consequences facing the ministry. Different statistical tools were used to analyze and process the data using (Amos -PSPS). Research methodology: The research used the analytical method to extract results based on the reality of applying the three research variables in the research ministry. Research Objective: To demonstrate the statistical relationships of the three research variables, organizational Ambidexterity as an independent variable, organizational consequences as an interactive variable and entrepreneurial behavior as a dependent variable. Results: The research concluded that there is an effect between its variables, the researched ministry’s interest in organizational ingenuity and its ability to face the consequences, whether internal or external, and enables it to exploit opportunities and achieve progress and excellence in performance.
Keywords: Organizational ambidexterity, organizational consequences , entrepreneurial behavior.